Uma metodologia para desenvolvimento de instrumentos de avaliação do construto satisfação do usuário em IHC - Cardador, Wellington Aparecido (2010)
The extensiveness of users that take advantage of interactive systems has reached parameters that never have seen before in recent history. Nowadays, a large number of people are able to access interactive devices outfitted with an interface and, considering the evolution of the technology, it tends to achieve practically any human being, not concerning about peculiarity or restrictions. Hence, there is a concern about usability warranty and to make it possible it must take advantage of the evaluation procedures. Performance measures (effectiveness and efficiency) and user satisfaction measures are accepted by literature as usability measures. It is possible quantifying performance measures by straight observing it. However, the user satisfaction factor cannot be observed at the same way because of its entirely subjective property. Unfortunately, the literature is based in subjective ways in order to evaluate the satisfaction construct in a manner that it is considered as in a situation of conceptually fragile area. The current context is that the user satisfaction construct is, in fact, not fully understood. The attempts for user evaluation are subjective because its still substantial dependency of user itself reports that, according to scientific methods, are biased and it is subordinated to the personal equation - the personal bias that underestimate or overestimate evaluations. Although it is arduous acquiring careful precision in user satisfaction construct evaluation, it is plausible to achieve almost real values, if appropriated procedures were applied. This work studies the user satisfaction evaluation problem by understanding the dimensions that comprises it and proposals a methodology for instruments construction aimed to evaluate the satisfaction, based on well established concepts in the literature as well as Usability Context Analysis, Psychometrics, Personas and Biometry. It was determined three steps: requirement analysis, specification and construction. Each step is composed of activities that purposes taking a merely subjective factor and turning it into liable mensuration indicators, then co-operating to objectivity in user satisfaction evaluations.